Pakistan : 2021 Article IV Consultation, Sixth Review Under the Extended Arrangement Under the Extended Fund Facility, and Requests for Waivers of Applicability and Nonobservance of Performance Criteria and Rephasing of Access-Press Release; Staff Report; and Statement by the Executive Director for Pakistan. (IMF Staff Country Reports; Country Report ;, 2022)
Economic activity has rebounded strongly on the back of waning COVID-19 infections and expansionary fiscal and monetary policies. However, strong import growth-fueled by the macroeconomic policy mix, higher international commodity prices, and credit growth-have led to a marked deterioration of the external position. The current account deficit has widened, the rupee depreciated markedly, and inflation remains persistently high.